Human KV interaction. - Neville-Neil, George (New York ACM, 2005)
A koder with attitude, KV answers your questions. Miss Manners he ain't.
Keywords: General literature; Software; Software engineering; Programming environments; Information systems; Information interfaces and presentation; Computing Milieux; Management of computing and information systems; Installation management